Expanding the Allelic Heterogeneity of ANO10-Associated Autosomal Recessive Cerebellar Ataxia. (23rd February 2023) - Massey, Sean; Guo, Yiran; Riley, Lisa G.; Van Bergen, Nicole J.; Sandaradura, Sarah A.; McCusker, Elizabeth; Tchan, Michel; Thauvin-Robinet, Christel; Thomas, Quentin; Moreau, Thibault; Davis, Mark; Smits, Daphne; et al.
Abstract : Background and Objectives: The term autosomal recessive cerebellar ataxia (ARCA) encompasses a diverse group of heterogeneous degenerative disorders of the cerebellum. Spinocerebellar ataxia autosomal recessive 10 (SCAR10) is a distinct classification of cerebellar ataxia caused by variants in the ANO10 gene. Little is known about the molecular role of ANO10 or its role in disease. There is a wide phenotypic spectrum among patients, even among those with the same or similar genetic variants. This study aimed to characterize the molecular consequences of variants in ANO10 and determine their pathologic significance in patients diagnosed with SCAR10. Methods: We presented 4 patients from 4 families diagnosed with spinocerebellar ataxia with potential pathogenic variants in the ANO10 gene. Patients underwent either clinical whole-exome sequencing or screening of a panel of known neuromuscular disease genes. Effects on splicing were studied using reverse transcriptase PCR to analyze complementary DNA. Western blots were used to examine protein expression. Results: One individual who presented clinically at a much earlier age than typical was homozygous for an ANO10 variant (c.1864A > G [p.Met622Val]) that produces 2 transcription products by altering an exonic enhancer site. Two patients, both of Lebanese descent, had a homozygous intronic splicing variant in ANO10 (c.1163-9A > G) that introduced a cryptic splice site acceptor, producing 2 alternative transcription products and no detectable wild-type protein. Both these variants have not yet been associated with SCAR10. The remaining patient was found to have compound heterozygous variants in ANO10 previously associated with SCAR10 (c.132dupA [p.Asp45Argfs*9] and c.1537T > C [p.Cys513Arg]). Discussion: We presented rare pathogenic variants adding to the growing list of ANO10 variants associated with SCAR10. In addition, we described an individual with a much earlier age at onset than usually associated with ANO10 variants. This expands the phenotypic and allelic heterogeneity of ANO10 -associated ARCA.